Problems in the planning and implementation of in-service education program of public elementary schools in the Division of South Cotabato - Perez, Jose Recto 1914- (s.n.], 1971)
One of the perplexing problems of the Division of South Cotabato is the inadequate number of administrative and supervisory personnel that can cope with the growth of enrolment and the vastness of the topography of the municipalities in the division. This investigation aimed to determine the problems in the planning and implementation of in-service education program of public elementary schools.